2022
DOI: 10.1002/cssc.202201809
|View full text |Cite
|
Sign up to set email alerts
|

Solvent Effects Enable Efficient Tandem Conversion of Cellulose and Its Monosaccharides Towards 5‐Hydroxymethylfurfural

Abstract: The biomass‐derived platform compound 5‐hydroxymethylfurfural (HMF) has been hailed as the “Sleeping Giant” due to its promising applications, and it occupies a critical spot in the biomass upgrading roadmap. HMF is typically produced from cellulose and its monosaccharides via a complex tandem conversion with multiple steps (i. e., cellulose depolymerization, glucose isomerization, fructose dehydration, etc.). Previous investigations have confirmed the irreplaceable contribution of solvents in regulating the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 128 publications
0
5
0
Order By: Relevance
“…C 6 furan compounds can be readily obtained through acidcatalyzed depolymerization of biomass polysaccharides and hydrolysis of monosaccharides. [63][64][65][66][67] The reaction systems regarding the above-mentioned processes have already been thoroughly investigated in the last decade, which have enabled the C 6 furan compounds to be accessible in large quantities from industrial production. 68,69 In the follow-up routes, some emerging investigations have been performed to form linear diketones, such as HD and HHD, through selectively promoting the ring-opening conversion of these furans.…”
Section: Basic Properties Of Biomassderived Linear Diketonesmentioning
confidence: 99%
“…C 6 furan compounds can be readily obtained through acidcatalyzed depolymerization of biomass polysaccharides and hydrolysis of monosaccharides. [63][64][65][66][67] The reaction systems regarding the above-mentioned processes have already been thoroughly investigated in the last decade, which have enabled the C 6 furan compounds to be accessible in large quantities from industrial production. 68,69 In the follow-up routes, some emerging investigations have been performed to form linear diketones, such as HD and HHD, through selectively promoting the ring-opening conversion of these furans.…”
Section: Basic Properties Of Biomassderived Linear Diketonesmentioning
confidence: 99%
“…Different classes of solvents have been employed in the conversion of cellulose into HMF, encompassing aqueous, organic, and ILs, in both mono and biphasic configurations (Tables 1, 4, 6). Each of these solvent types presents inherent advantages and disadvantages, which are elaborated upon as follows: [111] …”
Section: One‐pot Catalytic Conversion Of Cellulose To Hmf Using Heter...mentioning
confidence: 99%
“…Among the various solvents, EtOH is a potential alternative solvent considering its low cost, stability, and non-toxicity. 20,21 The conversion of fructose in a mixed solvent containing water and EtOH can tandemly convert HMF into the more stable EMF via etherification (Scheme 1), 22 leading to the co-production of EMF and HMF. For example, Russo et al 19 reported that the introduction of EtOH in water increased the total yield of EMF and HMF from 9% to 56% from fructose (5.9 wt%) catalyzed by a sulfonated carbon–silica composite catalyst at 170 °C for 4 h. Liu et al 23 reported the one-pot synthesis of EMF and HMF from fructose (0.9 wt%) over an MIL-101-SO 3 H(100) catalyst in a mixed solvent of EtOH and THF, resulting in a total yield of 76% after reaction at 130 °C for 15 h. Besides, the FeCl 3 -catalyzed conversion of fructose (3.6 wt%) in a mixed solvent of EtOH and 1-butyl-3-methylimidazolium chloride resulted in a high yield (90%) of EMF and HMF after reaction at 80 °C for 12 h. 24 Nevertheless, the imbalanced carbons of the products in these reported systems still demonstrated the loss of biomass-derived carbons by the formation of soluble humins.…”
Section: Introductionmentioning
confidence: 99%